well, the recursive rule of aₙ = aₙ₊₁ + 7, where a₁ = 15, is simply saying that
we start of at 15, and the next term is obtained by simply adding 7, and so on.
well, that's the recursive rule.
so then let's use that common difference and first term for the explicit rule.
![\bf n^(th)\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} a_n=n^(th)\ term\\ n=\textit{term position}\\ a_1=\textit{first term}\\ d=\textit{common difference}\\ \cline{1-1} a_1=15\\ d=7 \end{cases} \\\\\\ a_n=15+(n-1)7\implies a_n=15+7n-7\implies a_n=7n+8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iv5is50izyubwx6gsicixx425033wj06e6.png)